Environmental Activism and Cyber-advocacy on Social Media: A Case Study from Indonesia - Nurhadi Susanto; M.H. Thamrin (Magister Administrasi Publik, 2021)
This study contributes to a more comprehensive understanding of the functions of social media for ENGOs (Environmental Non-Government Organization). Recently, ENGOs’ presence on social media caught public attention due to the emergence of several offline protests that were initiated online. The research used content analysis on tweets posted by two ENGOs in Indonesia. The results showed that social media was used primarily to build public awareness regarding environmental issues in Indonesia. In this case, ENGOs tries to educate the public on the causes and consequences of environmental problems. One of the issues highlighted is infrastructure development which is currently underway in Indonesia. While infrastructure development fosters long term development, the process has been associated with detrimental effects on the environment. This research also found that the public can act as a vital source of informationon environmental issues. Social media allow the public to connect virtual with the real world , thereby giving them the opportunity to participate in policy debates even in the absence of physical presence. That said, while social media is an important alternative channel for communicating positions and ideals, ENGOs still principally rely on mainstream media to reach a broader public, largely due to the digital divide that prevents certain people from active participation.